A COMPARATIVE ANALYTICAL STUDY OF ENGLISH CHILDREN NOVEL ALICE’S ADVENTURES IN WONDERLAND WITH ITS TRANSLATION INTO ARABIC - Prof. Qasim Abbas Dhayef; Baraa Kareem Ghazi (Journals Park Publishing, 2022)
Translating from English into Arabic involves certain linguistic and cultural problems. In order to understand these problems, one has to return to the cultural and social background of the source language) English (texts and try to find out how these may affect the process of translating into Arabic.The research attempts to find answer(s) the following question: What are the basic problems of translation by comparing the English text with the Arabic text?This paper aims at: Finding out the basic problems of translation by comparing the English text with the Arabic text.It is hypothesized that the problems of translation from English to Arabic are cultural and linguistic ones.The methodology of the present study is that an English novel is taken as it is with its translation into Arabic. Then, the original text and the translated one are going to be analyzed comparatively.This study investigates the strategies used by translators when translating the famous children ‘s novel Alice’s Adventures in Wonderland by Lewis Carroll translated from English into Arabic.
Keywords: Comparative Linguistics; English; Arabic